1985
DOI: 10.1002/cber.19851180917
|View full text |Cite
|
Sign up to set email alerts
|

Strukturuntersuchungen zum System 1,3‐Dialkoxy‐2‐aza‐allenium‐Ionen/1,3‐Dialkoxy‐2‐aza‐allyl‐Kationen

Abstract: CationsThe title system (I/II) is experimentally accessible by regiospecific alkylation at the carbonyl oxygen of alkyl N-acylimidates 4 using txialkyloxonium salts. According to an X-ray investigation (3a), the salts 3 form a compromise structure between both isomeric forms, the alkoxy substituents being in exo positions in s-cis-conformations (C -N -C-bond angle 133.0", torsional angle 70.4'). Quantum mechanical calculations (3-21G ab initio) for the parent substance N-formylformimidic acid 6 a predict prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The iminium ion 3 ؉ exhibits a longer ''normal'' bond length (Xray: 1.29Å ; RHF/6-31G*: 1.281 Å ; B3LYP/6-31G*: 1.308 Å ), which is close to the standard data for CϭN bonds [18,20] involving an sp 2 -hybridized nitrogen atom. An analogue of the third system 2a ϩ [diphenyl instead of bis(p-tolyl)] with its two electron-donating ethoxy groups was subjected to an X-ray diffraction study some time ago; [11] the CϭN bond length obtained was 1.30 Å , (RHF/6-31G* 1.294 Å ; B3LYP/6-31G* 1.308 Å ), slightly longer than in 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The iminium ion 3 ؉ exhibits a longer ''normal'' bond length (Xray: 1.29Å ; RHF/6-31G*: 1.281 Å ; B3LYP/6-31G*: 1.308 Å ), which is close to the standard data for CϭN bonds [18,20] involving an sp 2 -hybridized nitrogen atom. An analogue of the third system 2a ϩ [diphenyl instead of bis(p-tolyl)] with its two electron-donating ethoxy groups was subjected to an X-ray diffraction study some time ago; [11] the CϭN bond length obtained was 1.30 Å , (RHF/6-31G* 1.294 Å ; B3LYP/6-31G* 1.308 Å ), slightly longer than in 3…”
Section: Discussionmentioning
confidence: 99%
“…- [11] in the solid state was already known. Preliminary experiments have indicated that this system is indeed relatively unreactive, which limits considerably the choice of suitable nucleophiles for kinetic studies.…”
Section: Kinetic Studiesmentioning
confidence: 95%
“…DFT calculations, AIM analysis, and Boys localized orbitals indicate that the long C(2)-F interaction is a dative bond and the unsymmetrical 188b structure must also contribute. [425][426][427][428][429][430][431] They are well-characterized and used widely in dipolar cycloadditions. The Si-containing ring system 194 analogous to 188 has been reported by M€ uller and co-workers.…”
Section: -Brmentioning
confidence: 99%
“…422 The silyl cation is stabilized by intramolecular interactions with the F atoms increasing the coordination number of Si and, consequently, Si becomes considerably shielded. 427 The 2-azaallyl structure 200 of the parent tetrahydroxy model compound (C 2 symmetry) was shown by quantum mechanical calculations to be 20 kcal mol À1 lower in energy than the corresponding 2-azoniaallene. Characteristic data for cation 194 are as follows: SiÀF bond lengths ¼ 1.…”
Section: -Brmentioning
confidence: 99%
“…The alkynyldihydroxycarbenium ions RC:C ± C + (OH) 2 (R = H, Me, Ph) arising upon protonation of the corresponding propiolic acids by FSO 3 H in liquid SO 2 (778 8C) or in SO 2 ClF (7120 8C) have been detected by NMR spectroscopy. 102 A fairly comprehensive study of the 13 C NMR spectra of a series of phenylethynylcarbenium ions (together with benzyl-and naphthylcarbenium cations) has been reported by Olah et al 103 They analysed in detail the degree of positive charge delocalisation as a function of the nature of the substituents at the carbenium centre. In particular, the 13 C NMR spectra of protonated carbonyl compounds 113 were discussed.…”
Section: Spectroscopic Studies Of Alkynyl Carbocationsmentioning
confidence: 99%